2020
DOI: 10.4149/bll_2020_028
|View full text |Cite
|
Sign up to set email alerts
|

Improving effects of mesenchymal stem cells on symptoms of chronic obstructive pulmonary disease

Abstract: AIM: We aimed to identify the improving effects of umbilical cord tissue-derived (UCTD) MSCs on the symptoms of COPD in our phase 1.2 clinical study. MATERIAL METHODS: Our study consisted of fi ve patients with COPD. Respiratory function tests, SGRQ symptom, activity and impact scores and 6-minute walk test (6MWT) were examined before UCTD MSC treatment. All the patients were administered a total of 4 doses of UCTD MSCs by intravenous infusion at two-week intervals. All the tests were repeated three months aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…There are two ways to solve this problem, that is by adjusting the schedule of administration or mode of administration. By comparing the two UC-MSCs trials, we found that multiple doses may have a better therapeutic effect than single dose [30,81] . Therefore, increasing the number of doses is an ideal improvement for future stem cell research.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…There are two ways to solve this problem, that is by adjusting the schedule of administration or mode of administration. By comparing the two UC-MSCs trials, we found that multiple doses may have a better therapeutic effect than single dose [30,81] . Therefore, increasing the number of doses is an ideal improvement for future stem cell research.…”
Section: Discussionmentioning
confidence: 97%
“…In recent years, the therapeutic effect of stem cells in animal models of COPD has been demonstrated by many preclinical studies, which mainly focus on BM-MSCs, AD-MSCs, and UC-MSCs [17,30] . People treat the experimental animals with different sources of stem cells, different methods, doses, and times of administration.…”
Section: Theoretical Basismentioning
confidence: 99%
See 2 more Smart Citations
“…Attempted solutions to this problem have included adjusting the schedule or mode of administration. However, the outcome of these attempts have not always been promising [ 10 , 11 ]. Therefore, other strategies to enable stem cells to stay longer in the lungs need to be considered.…”
Section: Introductionmentioning
confidence: 99%